Latent constructs in the measurement of risk and protective factors for violent reoffending using the HCR-20v3 and SAPROF: implications for conceptualizing offender assessment and treatment planning - Klepfisz, Gabrielle (Psychology, crime & law, 2020)
This paper describes a retrospective data analysis, examining the relationship between protective factors against violence, as measured by the Structured Assessment of Protective Factors for Violence Risk (SAPROF), and conceptually similar risk factors assessed in the Historical-Clinical-Risk Management-20 Version 3. The sample comprised 201 adult male violent offenders who completed a violence intervention programme in an Australian prison. Structural equation modelling revealed that conceptually similar risk and protective factors loaded onto correlated, but independent, factors. This suggests that these items from the two assessment tools may assess distinct latent constructs relevant to violence risk. SAPROF items did not, however, load onto the domains that are commonly targeted in violence treatment programmes. This study’s conclusion that assessment of protective factors may offer supplementary conceptual value in clinical practice with violent offenders is tempered by limitations, including the retrospective file review design, small sample, and lack of predictive validity of SAPROF ratings.